Clinical Efficacy of Selective Nerve Root Block in Lumbar Radiculopathy due to Disc Prolapse - Dhakal, Gaurav Raj; Hamal, Pawan Kumar; Dhungana, Siddhartha; Kawaguchi, Yoshiharu (Journal of Nepal Health Research Council, 2019)
Background: Selective Nerve Root Block using steroid is a proven technique for management of lumbar radiculopathy. The aim of the study was to determine the effectiveness of selective nerve root block in lumbar radiculopathy. Methods: A prospective observational study was conducted for duration of one year in patients diagnosed with lumbar radiculopathy. Patients with leg pain, positive straight leg raising test and single level disc prolapse were included in the study. The procedure was performed under fluoroscopic guidance and Visual Analogue Pain rating scale and Oswestry Disability Index score was used for assessment pre-injection, 1 week, 1 month, 6 months and 1-year post injection. Results: Total 35 patient with mean age of 37.7± 9.31 years were included in the study. The pre-injection Visual Analogue Pain Score(Mean ± S.D:7.8±0.7) was significantly reduced at one week (4.2±1.47, p <0.00001), one month (2.74±1.06, p <0.00001), six months (2.31±0.75, p <0.00001) and one year (2.62±0.84, p <0.00001). Similarly, pre-injection Oswestry Disability Index score (Mean ± S.D: 32.09±5.95) was significantly reduced at one week (19.51±7.26, p <0.00001), one month (12.71±4.56, p <0.00001), six months (9.8±2.87, p <0.00001) and one year (10.09±2.97, p <0.00001) but not significantly improved when compared at 6 months and 1 year (p < 0.44). Conclusions: Selective Nerve Root Block in lumbar radiculopathy significantly reduces Visual Analogue Pain Score up to a year, however, the reduction in pain plateaus around six months.Disability index score only reduces for first 6 months but doesn’t significantly reduce from six months to one year. Keywords: Lumbar; radiculopathy; selective nerve root block; steroid.